Urgensi Bantuan Hukum Relawan Pendamping, Pekerja Sosial Dan Serikat Buruh Setelah Putusan MA No. 22 P/HUM/ 2018 - Simarmata, Jorawati (Jurnal Hukum & Pembangunan, 2018)
The Supreme Court Decision No.22 P / HAM / 2018 has canceled Permenkumham Number 1 Year 2018 because it contradicts Law Number 18 Year 2003. However, there are several implementations and provisions of the Law that show the urgency of paralegal functions. The urgency of the paralegal function is shown by the high number of domestic violence cases caused by various aspects of life and the existence of the Domestic Violence Law and The Convention on All Forms of Discrimination Against Women which mandates the need for voluntary assistants function to handle domestic violence problems. Besides that it is proven that the function of social workers under the auspices of child protection institutions in the region effectively handles violence against children and the presence of mandate of the Convention on the Rights of the Child and Law No. 35 of 2004 to protect children who are faced with the law by providing social workers. Then there is the mandate of Article 28 of the 1945 Constitution, ILO Convention No. 87, and ILO Convention No. 98 which provide guarantees to labour to establish labour unions in dealing with industrial relations disputes.